Amperometric Detection of dsDNA using an Acridine‐Orange‐Modified Glucose Oxidase. Issue 11 (10th October 2017) - Jambrec, Daliborka; Lammers, Klaus; Bobrowski, Tim; Pöller, Sascha; Schuhmann, Wolfgang; Ruff, Adrian
Abstract: Invited for this month's cover is the group of Prof. Dr. Wolfgang Schuhmann, Dr. Daliborka Jambrec and Dr. Adrian Ruff at Ruhr‐Universität in Bochum, Germany. The cover picture shows a novel procedure for the preferential post‐hybridization labeling of double‐stranded DNA based on the intercalating compound acridine orange, which was covalently bound to glucose oxidase. Labeling with a highly active biocatalyst allows for a simple and sequence‐independent amplification of the signal proportional to the amount of hybridized DNA that may be coupled with other amplification strategies. Read the full text of the article at 10.1002/cplu.201700279 . Abstract : "We created an alternative DNA post‐hybridization labeling strategy based on a specific intercalating compound that was covalently bound to a highly active redox enzyme providing the basis for electrochemical readout." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI:10.1002/cplu.201700279 ).